Horizons in Neuralgia Care: Addressing Unmet Needs and Future Prospects - Pramod Kumar Pathak; Satish Kumar Sarankar (International Journal of Brain Sciences, 2025)
Neuralgia refers to intense, sharp, and often chronic pain resulting from damage or irritation to nerves. It is typically characterized by sudden, shooting pain along the course of a nerve, significantly impairing daily functioning and impacting both physical and emotional well-being. Given its intensity and chronic nature, neuralgia presents a complex challenge in clinical management, emphasizing the importance of timely diagnosis and effective intervention to improve patient outcomes. This comprehensive overview covers the underlying causes, types, clinical manifestations, diagnostic strategies, and treatment options for neuralgia. Various etiologies are explored, including nerve compression, viral infections (such as shingles), diabetes, multiple sclerosis, and traumatic injuries, all of which can lead to nerve irritation or damage. The discussion includes distinct forms of neuralgia, such as trigeminal, postherpetic, glossopharyngeal, and occipital neuralgia, each associated with specific pain patterns and nerve involvement that necessitate tailored diagnostic and therapeutic approaches.Clinically, neuralgia is marked by sudden, sharp, and stabbing pain, often triggered or exacerbated by touch, temperature changes, or movement. Symptoms may be intermittent or persistent, complicating the clinical presentation and making diagnosis more challenging. Diagnostic strategies emphasize thorough clinical evaluations, detailed patient histories, and the use of advanced imaging techniques like MRI and CT scans to identify underlying causes. In some cases, nerve conduction studies or electromyography are employed to assess nerve damage or dysfunction. Treatment options range from pharmacological therapies, including anticonvulsants, antidepressants, and analgesics, to interventional approaches like nerve blocks, neuromodulation, and surgical procedures. Each modality is examined in terms of efficacy, limitations, and potential side effects, reinforcing the need for individualized treatment plans based on the specific type and severity of neuralgia. By offering an in-depth exploration of neuralgia’s causes, clinical features, diagnostic methods, and treatment strategies, this article aims to enhance understanding and improve management practices. It also underscores the ongoing need for research into novel and more effective therapies to better address the complexities of neuralgia and reduce its burden on patients.
Keywords: Neuralgia; Peripheral neuropathy; diagnosis; management; treatment